Pengaruh penambahan tepung buah mengkudu (Morinda citrifolia L.) dalam pakan terhadap penampilan produksi itik Hibrida - Bayu Widianto; Heni Setyo Prayogi; Nuryadi Nuryadi (Faculty of Animal Science, Universitas Brawijaya, 2015)
This research was conducted to investigate the effect of noni fruit powder (Morinda citrifolia .L.) addition in feed on production performance of hybrid ducks such as feed consumption, body weight gain and feed conversion ratio. Ninety six 14-days old hybrid ducks were used in this research. The hybrid duck was reared until 54-days old. The research method was experimental using Completely Randomized Design (CRD) with four treatments and six replications, each replication consisted of four hybrid ducks. The treatments consisted of P0 (Basal feed), P1 (Basal feed + 1% noni fruit powder), P2 (Basal feed + 2% noni fruit powder) and P3 (Basal feed + 3% noni fruit powder). The data were analyzed using ANOVA and continued by Duncan's multiple range test if there were significantly different results. The results showed that noni fruit powder did not give significant effect (P>0.05) on production performance of hybrid ducks such as feed consumption, body weight gain and feed conversion rate. The research concluded that supplementation of noni fruit powder (Morinda citrifolia L.) in feed up to level 3% did not significantly increase production performance of hybrid ducks. However, the addition of noni fruit powder (Morinda citrifolia L.) at the level of 2% showed the best results on feed consumption (4508.79 ± 106.22), body weight gain (1006.29 ± 36.14) and feed conversion ratio (FCR) (4.49 ± 0.24). Keywords : noni fruit powder, production performance and hybrid ducks